The investigation of additive manufacturing and moldable materials to produce railway ballast grain analogs (Fracture and Structural Integrity, 2022)
The size and shape of individual grains, play an important role in the mechanical behavior of granular materials such as the strength and stability of railway ballast. The aim of this research is to study materials from which uniform, reproducible grains with irregular convex geometry can be created by molding and additive manufacturing technologies in order to create reproducible artificial assemblies that can be used in experiments. Packings with determined grain shape results more controlled investigations contrarily to using natural grains with random geometry. Specimens were made from railway ballast materials, materials used in the construction industry, additively manufactured and molded polymers, and certain low-strength materials. Uniaxial compression and bending tests were conducted on these specimens. The mechanical properties of typical railway ballast materials (basalt and andesite) were compared with the properties of artificially produced materials. The results show that for grain reproduction the molding technology is recommended with the use of polyester-crushed stone composite and ceramic powder. Furthermore, the additive manufacturing was recommended with PolyJet or Multi Jet Fusion technology as they have the feasibility to produce grains with similar material properties to the properties of basalt and andesite.
Keywords: Granular materials; Railway ballast; 3D printing; Effect of shape; Uniaxial compression test; Grain breakage